The Formation of Perceived Meaning on Essential Matters in The Little Prince - Tania Gissela Susilo (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This study analyzes the correlation of social interactions and their role in forming one’s perceived meanings of the essentials in life in The Little Prince. Using Herbert Blumer’s (1969) Symbolic Interactionism Theory, I analyze the processes during their social interactions, the meanings generated, the interpretation of meanings, and how meanings become the basis of one’s actions. My analysis reveals their social interactions before the encounter generate perceived meanings on essential matters, which drive their lives. The Aviator, perceiving the essentials from interactions with an industrialized society, lives a mundane and lonely life—whilst the Little Prince, perceiving the essentials come from the heart, lives a fulfilled life. However, their encounter alters the Aviator’s perceived meaning, creating a shared perceived meaning on essential matters. Ultimately, the shared perceived meaning drives their actions—the Aviator shares it with the readers and the Little Prince develops the way he expresses it with his friends.